Mobility in the Developing Country. The Case Study of Bangkok Metropolitan Region - Kamil Wilinski; Shubham Pathak (Communications, 2022)
Significant economic growth visible in recent decades in Thailand contributed to a huge demand for private vehicles, which was not followed by a sufficient growth of transport infrastructure, consequently leading to permanent congestion, increase in the number of accidents, high carbon emission and thus a decline in the air quality. This research was conducted in the capital of Thailand, Bangkok using key informant interviews to examine socio-economic determinants of 3 different modes choice: car, motorcycle and public transport. The major findings included the lack of use of public transportation due inadequate transportation schemes and policies at the local and national level in Thailand. Further analytical findings include the social, cultural and economic factors affecting the choices of the mode of transportation in Thailand.